The Spirit of the Anti-Corruption Movement in the Campus Environment Through Various Community Creativity Social Media Movements (Journal of Creativity Student, 2022)
The causes of corruption include weak religious teachings, ethics, knowledge, education, and the imposition of sanctions and a weak government structure. Eradication of corruption can be done through education, because education has a very strategic position in an effort to build an anti-corruption attitude, especially to the younger generation. In this case, students have a role to not be permissive of corruption and together rise up against corruption. The research method in this paper uses qualitative research methods from individual and institutional journalistic sources, and the research uses empirical methods with a discussion technology-based approach, namely the Zoom Meeting application/web to find data from lighters and respondents. The purpose of this paper is to understand the causes of corruption and to find out why students should build the spirit of the anti-corruption movement in the campus environment. With the conclusion that someone commits acts of corruption because of factors both from within and from outside. so that students have a role in encouraging and inviting the public to act to create justice so that corruption does not occur.